The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.molcel.2006.12.012
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Independent PARP-1 Activation by Phosphorylated ERK2 Increases Elk1 Activity: A Link to Histone Acetylation

Abstract: PolyADP-ribose polymerases (PARPs) catalyze a posttranslational modification of nuclear proteins by polyADP-ribosylation. The catalytic activity of the abundant nuclear protein PARP-1 is stimulated by DNA strand breaks, and PARP-1 activation is required for initiation of DNA repair. Here we show that PARP-1 also acts within extracellular signal-regulated kinase (ERK) signaling cascade that mediates growth and differentiation. The findings reveal an alternative mode of PARP-1 activation, which does not involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
297
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(323 citation statements)
references
References 41 publications
26
297
0
Order By: Relevance
“…However, several alternative mechanisms leading to the activation of PARP1 in the absence of DNA damage have also been described [39][40][41][42]. Here we have shown that a low concentration of hydrogen peroxide produced "physiologically" by cells induced to undergo osteodifferentiation is sufficient to induce DNA breakage as evidenced by the comet assay.…”
Section: Discussionsupporting
confidence: 52%
“…However, several alternative mechanisms leading to the activation of PARP1 in the absence of DNA damage have also been described [39][40][41][42]. Here we have shown that a low concentration of hydrogen peroxide produced "physiologically" by cells induced to undergo osteodifferentiation is sufficient to induce DNA breakage as evidenced by the comet assay.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, PARP-1 contributes to NF-B activation in the inflammatory response, provoking CREB binding protein recruitment independent of poly[ADP]-ribosylation (Hassa et al, 2005). In contrast, PARP-1 enzymatic activity is need for the recruitment of coactivators to Elk-1 and Hes-1 during neuronal activation and neurogenesis, respectively (Ju et al, 2004;Cohen-Armon et al, 2007). It has also been shown that PARP-1 contributes to chromatin remodeling and gene transcription in Drosophila under certain physiological conditions (Tulin and Spradling, 2003), probably by releasing histone H1 from specific promoters (Krishnakumar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, this is a consequence, at least in part, of the negative charge that the modification confers to the histone. In addition, though, it has been reported that the activation of PARP-1 leads to elevated levels of core histone acetylation [39]. Moreover, PARP-1-mediated ribosylation of the H3K4me3 demethylase KDM5B inhibits the demethylase and excludes it from chromatin, while simultaneously excluding H1, thereby making target promoters more accessible [40].…”
Section: Adp Ribosylationmentioning
confidence: 99%